Standards and open source technology of NFV - Shuhui MA; Tao WU (Dianxin kexue)
In recent years，many influential international and domestic standard organizations have established special working groups to research NFV related standards as an emerging technology.Meanwhile a batch of NFV related open source organizations have been produced on the basis of standard research and development.Related standard organizations followed by ETSI and many open source organizations represented by OPNFV were tracked and studied，and the latest achievements were further researched.And then the development trend of NFV standards was deeply analyzed.Finally，the key open source technologies of NFV architecture were summarized.